Novel MASP1 mutations are associated with an expanded phenotype in 3MC1 syndrome. Issue 1 (December 2015) - Atik, Tahir; Koparir, Asuman; Bademci, Guney; Foster, Joseph; Altunoglu, Umut; Mutlu, Gül; Bowdin, Sarah; Elcioglu, Nursel; Tayfun, Gulsen; Atik, Sevinc; Ozen, Mustafa; Ozkinay, Ferda; et al.
Abstract Background 3MC1 syndrome is a rare autosomal recessive disorder characterized by intellectual disability, short stature and distinct craniofacial, umbilical, and sacral anomalies. Five mutations inMASP1, encoding lectin complement pathway enzymes MASP-1 and MASP-3, have thus far been reported to cause 3MC1 syndrome. Only one previously reported mutation affects both MASP-1 and MASP-3, while the other mutations affect only MASP-3. Methods We evaluated six unrelated individuals with 3MC1 syndrome and performed Sanger sequencing for all coding exons ofMASP1. We also measured complement lectin and alternative pathway activities in an affected individual's serum. Results We found two novel splice site mutations, c.1012-2A > G in one and c.891 + 1G > T in two probands, and three novel missense mutations, c.1451G > A (p.G484E), c.1657G > A (p.D553N), and c.1987G > T (p.D663Y). Missense mutations affect only MASP-3, while splice site mutations affect both MASP-1 and MASP-3. In a proband who is homozygous for c.891 + 1G > T, we detected a total lack of lectin complement pathway activity and a 2.5-fold lower alternative pathway activity. The phenotype observed in patients whose both MASP-1 and MASP-3 are affected and in those whose only MASP-3 is affected does not appear to be different. We observed structural brain abnormalities, neonatal tooth, a vascular anomaly and a solid lesion in liver as novel phenotypic features of 3MC1 syndrome. Conclusion Novel mutations and additional phenotypic features expand the genotypic and phenotypic spectrum of 3MC1 syndrome. Although patients with MASP-1 dysfunction in addition to disrupted MASP-3 have an altered complement system, their disease phenotype is not different from those having only MASP-3 dysfunction.